Abruptly autofocusing property of circular Pearcey vortex beams with different initial launch angles in harmonic potentials - Liu, Xianglian; Zhang, Di; Zhao, Lijiao; Li, Pu; Zhang, Jianguo; Liu, Yu (Oficyna Wydawnicza Politechniki Wrocławskiej, 2022)
We have studied and explored the influence of different launch angles on the circular Pearcey beams (CPBs) without vortex or with vortex for the first time. Although launch angles can manipulate the focal length and the contrast of peak intensity of the CPBs, the shape and propagation trajectory of the CPBs maintain invariant. When the vortex is considered, the focal pattern and the contrast of peak intensity of the circular Pearcey vortex beams (CPVBs) can be changed by adjusting the magnitude of topological charges and the position of vortex. In addition, we have deliberated the propagation of the CPVBs under the action of double opposite optical vortices.
Optica Applicata, Vol. 52, 2022, nr 3, s. 417-428
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; autofocusing beam; optical vortices; Pearcey